2013
DOI: 10.1021/jp311795b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvent on the Self-Assembly of Dialanine and Diphenylalanine Peptides

Abstract: Diphenylalanine (FF) is a very common peptide with many potential applications, both biological and technological, due to a large number of different nanostructures which it attains. The current work concerns a detailed study of the self-assembled structures of FF in two different solvents, an aqueous (H2O) and an organic (CH3OH) through simulations and experiments. Detailed atomistic molecular dynamics (MD) simulations of FF in both solvents have been performed, using an explicit solvent model. The self-assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 48 publications
7
102
1
Order By: Relevance
“…However, the difference between the two solvents for AA was substantially smaller. The simulation results showed good qualitative agreement with experimental observations (Rissanou et al, 2013). Alternatively, Guo et al implemented extensive CGMD simulations to probe the assembly of FF.…”
Section: Peptidessupporting
confidence: 63%
“…However, the difference between the two solvents for AA was substantially smaller. The simulation results showed good qualitative agreement with experimental observations (Rissanou et al, 2013). Alternatively, Guo et al implemented extensive CGMD simulations to probe the assembly of FF.…”
Section: Peptidessupporting
confidence: 63%
“…However, if one is interested in the static properties of the system (as is the case with the self-assembly problem of SFA diblocks), one can maintain the atomistic representation by resorting to MC, in which the configurational space is sampled by attempting moves that are often artificial or unphysical. MC has been used as an alternative to MD (Tamamis et al, 2009;Rissanou et al, 2013) to simulate several polymer-like systems, often with spectacular results. We mention, for example, the problem of self-assembly of short alkanethiols on metallic substrates (Alexiadis et al, 2007;: through a novel algorithm incorporating highly sophisticated moves such as atom identity exchange, configurational bias, and intramolecular double rebridging, a totally random initial configuration of an alkanethiol on a Au(111) substrate was found to be led to a final state characterized by the formation of a highly Table 1 Values of the molecular model parameters defining the potential energy function used in this work.…”
Section: Methodsmentioning
confidence: 99%
“…Although the same forces should affect the PND structure, we expect that inside a PND the packing is less optimal and hence the number of FF molecules can be significantly lower. The influence of solvent on the forces between the FF molecules in the process of self-assembly was recently demonstrated by Rissanou et al 27 Since both, simulations and experiments, indicate susceptibility for self-assembly, one can estimate the number of FF molecules inside a PND to be between 2 (a dimer) and 10. However, molecular dynamic simulations performed by Shell and co-workers 28 showed that FF molecules in a polar solvent can form dimers to hexamers, where the dimer configuration is the most frequent one having ∼70% probability, which is consistent with experimental data.…”
Section: -25mentioning
confidence: 95%